Cartel land [videorecording (DVD)] - Heineman, Matthew (Paramount Pictures, 2016)
In the Mexican state of Michoacá́n Dr. José Mireles, a small-town physician known as "El Doctor," leads the Autodefensas, a citizen uprising against the violent Knights Templar drug cartel. Meanwhile, in Arizona's Altar Valley, Tim "Nailer" Foley, an American veteran, heads a small paramilitary group called Arizona Border Recon, whose goal is to stop Mexico's drug wars from seeping across our border.